2012
DOI: 10.3960/jslrt.52.121
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressing Fatal Adult Multi-Organ Langerhans Cell Histiocytosis Complicated with Fatty Liver Disease

Abstract: Langerhans cell histiocytosis (LCH) is a clonal neoplasm that shows diverse clinical manifestations and courses of disease progression. The etiology and pathophysiology of LCH remain uncertain. We describe the clinical course of a 23-year-old Japanese woman with multi-system LCH, who showed rapid progression after steroid reduction and developed multi-organ failure. Liver biopsy showed LCH infiltration with fatty degeneration. She was treated with cytarabine, vincristine, and prednisolone according to the Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Langerhans cell histiocytosis is characterized by cells similar to bone marrow-derived Langerhans cells infiltrated in various tissues and organs [38]. Nonalcoholic fatty liver disease originates from hyperlipidemia, leading to liver failure and Langerhans cell histiocytosis infiltration [39]. In the present study, hepatic Langerhans cell histiocytosis was also observed in liver sections of untreated HFD-fed rats.…”
Section: Hfd-fed Group Treated With Chitosan (Hfd+cos)supporting
confidence: 61%
“…Langerhans cell histiocytosis is characterized by cells similar to bone marrow-derived Langerhans cells infiltrated in various tissues and organs [38]. Nonalcoholic fatty liver disease originates from hyperlipidemia, leading to liver failure and Langerhans cell histiocytosis infiltration [39]. In the present study, hepatic Langerhans cell histiocytosis was also observed in liver sections of untreated HFD-fed rats.…”
Section: Hfd-fed Group Treated With Chitosan (Hfd+cos)supporting
confidence: 61%
“…85 It should be noted that although most generally have indolent and chronic clinical courses, some adult LCH patients exhibit rapid progression and fatal courses. 86 However, the optimal systemic therapy for adult LCH has not yet been developed. [87][88][89][90] Multifocal adult LCH is an orphan disease.…”
Section: Adult Lchmentioning
confidence: 99%
“…Systemic chemotherapy is required for multifocal SS or MS disease also in adults . It should be noted that although most generally have indolent and chronic clinical courses, some adult LCH patients exhibit rapid progression and fatal courses . However, the optimal systemic therapy for adult LCH has not yet been developed .…”
Section: Treatment and Outcomementioning
confidence: 99%
“…LettererSiwe disease is seen in infants (usually within the first year of life), but occurrence in adult has been reported. 24,25 These patients present with fever, weight loss, pancytopenia, lymphadenopathy, hepatosplenomegaly, cuta neous lesions, and bone lesions. HandSchüllerChristian disease is seen in younger children who present with osteo lytic skull lesions, diabetes insipidus (due to hypopituita rism), and exophthalmos.…”
Section: Clinical Featuresmentioning
confidence: 99%